2004
DOI: 10.1073/pnas.0308071100
|View full text |Cite
|
Sign up to set email alerts
|

A germ-line insertion in the Birt–Hogg–Dubé ( BHD ) gene gives rise to the Nihon rat model of inherited renal cancer

Abstract: A rat model of hereditary renal carcinoma (RC) was found in a rat colony of the Sprague-Dawley strain in Japan and named the ''Nihon'' rat. In heterozygotes, RCs, predominantly the clear cell type, develop from early preneoplastic lesions, which began to appear as early as 3 weeks of age, to adenocarcinomas by the age of 6 months. The Nihon rat is an example of a Mendelian dominantly inherited predisposition for development of RCs like the Eker (Tsc2 gene mutant) rat. We have previously shown that the Nihon mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 16 publications
1
74
0
Order By: Relevance
“…Homozygous mutants are embryonic lethal in both Eker and Nihon rats (Okimoto et al, 2004a). In 2004, we identified a germline mutation in the rat homolog of BHD (Bhd) (Okimoto et al, 2004b). Subsequently, we demonstrated a suppression of the Nihon rat's phenotypes by transgenic introduction of a wild-type Bhd mini-gene (Togashi et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Homozygous mutants are embryonic lethal in both Eker and Nihon rats (Okimoto et al, 2004a). In 2004, we identified a germline mutation in the rat homolog of BHD (Bhd) (Okimoto et al, 2004b). Subsequently, we demonstrated a suppression of the Nihon rat's phenotypes by transgenic introduction of a wild-type Bhd mini-gene (Togashi et al, 2006).…”
Section: Introductionmentioning
confidence: 93%
“…A mouse monoclonal anti-HA (12CA5) antibody was from Roche. Anti-Flcn C1 antibody was reported previously (Okimoto et al, 2004b). Rabbit polyclonal anti-Flcn 223 antibody was generated against a synthetic peptide (CNTAFTPFLHQRNGNAARSL) corresponding to aminoacid residues (aa) 223-241 of human Flcn (IBL, Fujioka Japan).…”
mentioning
confidence: 99%
“…However, folliculin homologs were identified in many species, including Drosophila, Caenorhabditis elegans, mouse, dog and rat, implying a critical biological role for folliculin. Moreover, germline mutation in the rat and dog homologs of the BHD gene also resulted in inherited kidney tumors (Lingaas et al, 2003;Okimoto et al, 2004), suggesting that the BHD gene has a tumor suppressor function. Furthermore, recent evidence of somatic second-'hit' mutations in renal tumors from BHD patients (Vocke et al, 2005) strongly supports the Knudson 'two-hit' tumor suppressor model for BHD.…”
Section: Introductionmentioning
confidence: 99%
“…Establishment of transgenic Nihon rats carrying wild-type Bhd transgene We reported that rat Bhd gene consists of 13 exons and shows CpG island-like property near exon 1 (Okimoto et al, 2004b). In addition, we detected promoter activity in a 0.75 kb 5 0 -upstream sequence in cultured cells by reporter assay (our unpublished observation).…”
Section: Resultsmentioning
confidence: 89%
“…Sequence analysis revealed that there was an insertion of a cytosine (C) in a C tract within exon 3. This germline mutation results in a frameshift and produces a stop codon 26 amino-acids downstream (Okimoto et al, 2004b).…”
Section: Introductionmentioning
confidence: 99%